2017
DOI: 10.5812/zjrms.7911
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Feature of the Human Brucellosis Prevalence in People in Southern Cities of Khorasan Razavi, Iran

Abstract: Background: Brucellosis is one of the most important zoonoses in humans. Objectives: The purpose of our study was to identify factors affecting the incidence of brucellosis in human society and proposing a plan to reduce the burden of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The study results showed that 47.72% and 52.27% of the patients were rural and urban residents, respectively. Also, the results of the study showed a 40.9% prevalence in housewives, which is in agreement with the findings of Ramazani (26) and Karimi (18). They reported that most cases of brucellosis occurred among housewives (35.3% and 28.7%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The study results showed that 47.72% and 52.27% of the patients were rural and urban residents, respectively. Also, the results of the study showed a 40.9% prevalence in housewives, which is in agreement with the findings of Ramazani (26) and Karimi (18). They reported that most cases of brucellosis occurred among housewives (35.3% and 28.7%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…After many days, leads to acute complications such as tissue necrosis and hemolysis that eventually cause death (16). The prevalence of Compsobuthus matthiesseni species in the present study was similar to that of other studies in Iran (2,3,12,13,16,17,19). Two cases of Simonoides farzanpay species were found in the Barmeh Sabz village.…”
Section: Discussionsupporting
confidence: 89%
“…Scorpions are nocturnal arachnids with worldwide distribution from tropical to temperate, including deserts, savannas, tropical forests, and mountains over 5500 m in altitude, and the intertidal areas, and because they attack humans and are considered a threat to their lives (1,2). Scorpions are of various lengths and sizes, ranging from 13 to 220 mm, and their morphologic structures are easily identifiable (3).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zeinalian Dastjerdi et al (2012), given the risk of contact with infected animals and their products, the mean age of the affected cases was 31.3 years 23 . Nevertheless, other studies have reported a peak of cases in the age group older than 50 years 20 .…”
Section: Discussionmentioning
confidence: 82%